Sensors and Technologies in Spain: State-of-the-Art - Gonzalo Pajares (Sensors, 2014)
The aim of this special issue was to provide a comprehensive view on the state-of-the-art sensor technology in Spain. Different problems cause the appearance and development of new sensor technologies and vice versa, the emergence of new sensors facilitates the solution of existing real problems. [...]